1998
DOI: 10.1177/030089169808400117
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Stromal Tumors: A “Benign” Tumor with Hepatic Metastasis after 11 Years

Abstract: Gastrointestinal stromal tumors (GIST) constitue the largest category of primary non-epithelial neoplasms of the stomach and small bowel. They are characterized by a remarkable cellular variability and their malignant potential is sometimes difficult to predict. Very recent studies, using mitotic count and tumor size as the best determinants of biological behavior, divide GISTs into three groups: benign, borderline and malignant tumors. We report on a male patient who underwent a right hepatectomy for a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…GISTs are the most common mesenchymal tumors of the human gastrointestinal tract which are enigmatic in terms of their line of differentiation or cell of origin and clinical behavior [5] . Recently, many studies have shown that tumor size, location, mitotic cell count, cell type, proliferative activity, presence of necrosis, presence of hemorrhage, microscopic invasion to adjacent tissues, recurrence, distant metastasis, as favorable factors of GIST.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…GISTs are the most common mesenchymal tumors of the human gastrointestinal tract which are enigmatic in terms of their line of differentiation or cell of origin and clinical behavior [5] . Recently, many studies have shown that tumor size, location, mitotic cell count, cell type, proliferative activity, presence of necrosis, presence of hemorrhage, microscopic invasion to adjacent tissues, recurrence, distant metastasis, as favorable factors of GIST.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…However, they do not always reliably predict patient outcomes. Therefore, the designation, 'uncertain malignant potential', applies to a significant number of GISTs; close follow-up is needed in such cases [1,8,18,25]. Recently, some studies suggested that the disease-free survival of patients with c-kit mutation-positive GISTs was poorer than those with c-kit mutation-negative GISTs [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 50 malignant GIST, the survival was 84% at 1 year, 51% at 3 years and 41% at 5 years [4]. In general, it is difficult to predict the malignant potential and recurrence rate of GIST, hence long-term follow-up is essential [13]. …”
Section: Discussionmentioning
confidence: 99%